Evaluation of Analgesic Activity of Ficus Palmata: Evaluation of Analgesic activity of Ficus palmata - Aminabee, Skaik; Rao, A. Lakshmana; Sowmya, K.; Nymisha, D.; Naga Lakshmi, K. Kusuma; Manikanta, K.V.N.S.; Kumar, P. Praveen (Iranian Journal of Pharmaceutical Sciences, 2019)
Ficus palmata (FI) is an important and widely used medicinal plant. It is principally used as an item of diet in the treatment of constipation and diseases of the lungs and bladder. The sap is used in the treatment of warts. Ficus palmata plant is used in various disease e.g. gastrointestinal, hypoglycemic, antitumor, anti-ulcer, anti-diabetic, lipid lowering and antifungal activities. This study evaluates both the central and peripheral analgesic effect of the different extracts of Ficus palmata in the experimental animals. Methods: Acute toxicity test was done following the Organization of Economic Cooperation and Development guidelines. Ficus palmata extracts (250 mg/kg, 500 mg/kg) body weight was evaluated for central analgesic activity by the hot plate method, tail immersion method and formalin test models using tramodol (20 mg/kg b.w.) as the standard drug. Results: In all the models, chloroform extract showed significant inhibition as well as the elongation of time at a dose of 500 mg/kg body weight. A linear dose response relationship was also observed which was comparable with that of the standard drug tramodol (p<0.01, p<0.05). Conclusion: The study showed significant central and peripheral analgesic activity of Ficus palmata which may be attributed to the inhibition of prostaglandin synthesis, phospholipase A2, and tumor necrosis factor alpha. Ficus plamata as a commercial source of analgesic drug should be subjected to further research.